Solve (x + 2)(x+3) = (2x+4)

  • Google+ icon
  • LinkedIn icon

Expand: x2 + 2x + 3x +6 = 2x+4

Take (2x+4) from both sides: x2+3x+2 = 0

Facorise: (x+2)(x+1) = 0

So solutions are x=-2 and x=-1

Michael T. A Level Maths tutor, GCSE Maths tutor, A Level Computing t...

About the author

is an online GCSE Maths tutor with MyTutor studying at Durham University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss